(untitled) (Bangladesh Journal of Botany, 2008)
Cylindrocyctis brebissonii Menegh. and C. crassa var. elliptica West and West have beenillustrated and discribed in this paper as new report for Bangladesh. Key words: Phytoplankton, Cylindrocystis brebissonii, Cylindrocystis crassa var. elliptica, Saccoderm desmid, New record, Bangladesh doi:10.3329/bjb.v37i2.172 Bangladesh J. Bot. 37(2): 189-191, 2008 (December)